Effect of Independence, Work Experience and Competence on Audit Quality with Professional Ethics as Moderating Variable - Diyan Hera Prasanti; Wita Ramadhanti; Novita Puspasari (Jurnal Akuntansi Aktual, 2019)
Abstract: This study aims to examine the effect of independence, work experience and competence on audit quality with professional ethics as a moderating variable in public accounting firms in DKI Jakarta. The population in this study were all auditors at the Public Accounting Office in DKI Jakarta. The sample of this study amounted to 80 obtained from the determination of the sample using the purposive sampling method. This is a survey research with primary data derived from questionnaires distributed to the Public Accounting Firm in DKI Jakarta. Data analysis for hypothesis testing was performed using SPSS 16 with multiple linear regression and Moderated Regression Analysis. The results of this study indicate that: Work experience has a positive effect on audit quality, competence has a positive effect on audit quality, professional ethics strengthens the influence of work experience on audit quality, and professional ethics strengthens the influence of competence on audit quality.Abstrak: Penelitian ini bertujuan untuk menguji pengaruh independensi, pengalaman kerja dan kompetensi pada kualitas audit dengan etika profesional sebagai variabel moderasi di kantor akuntan publik di DKI Jakarta. Populasi dalam penelitian ini adalah semua auditor di Kantor Akuntan Publik di DKI Jakarta. Sampel penelitian ini berjumlah 80 yang diperoleh dari penentuan sampel menggunakan metode purposive sampling. Ini adalah penelitian survei dengan data primer yang berasal dari kuesioner yang didistribusikan ke Kantor Akuntan Publik di DKI Jakarta. Analisis data untuk pengujian hipotesis dilakukan menggunakan SPSS 16 dengan regresi linier berganda dan Analisis Regresi Moderated. Hasil penelitian ini menunjukkan bahwa: Pengalaman kerja memiliki efek positif pada kualitas audit, Kompetensi memiliki efek positif pada kualitas audit, Etika profesional memperkuat pengaruh pengalaman kerja pada kualitas audit, dan Etika profesional memperkuat pengaruh kompetensi pada kualitas audit.